(untitled) - Carne, Paul (Cambridge, U.K., 1997)
This collection of four complte practice tests for the revised Cambridge First Certificate in English examination. The practice tests follow precisely the specifications of the 1996 syllabus
Keywords: English language,English language,English language,Test of english as a foreign language; Examinations,Study and teaching